EFFECT OF INM ON NUTRIENTS UPTAKE AND YIELD OF MAIZEWHEAT CROPPING SEQUENCE AND CHANGES IN NUTRIENT AVAILABILITY IN TYPIC HAPLUSTEPTS - Madhavi,Kumari (The Bioscan, 2022)
Integrated nutrient management (INM) is an important tool to sustain of nutrients availability plants and improve soil fertility without any risk to environment. Field experiments were carried out during 2014-15 and 2015-16 under the ongoing AICRP on LTFE with Maize-Wheat cropping in Typic Haplustepts that initiated during kharif 1997 at the Instructional Farm of Rajasthan College of Agriculture, Udaipur. The experiment consisted of 12 treatment combinations viz., T1- Control, T2- 100%N, T3- 100%NP, T4- 100%NPK, T5- 100%NPK + Zn,